2015
DOI: 10.1002/pen.24239
|View full text |Cite
|
Sign up to set email alerts
|

Dual drug spatiotemporal release from functional gradient scaffolds prepared using 3D bioprinting and electrospinning

Abstract: Functional gradient scaffolds play an important role in osteochondral tissue engineering because they can meet the essential requirement for a gradual transition of both physical and chemical properties in osteochondral tissue regeneration. There is a requirement for 3D composite osteochondral regeneration scaffolds with multiscale structures that are capable of controlling release of multiple biomolecules. To this end, this article describes a 3D bioprinting platform integrated forming system designed to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Electron micrographs of the two samples are shown in Fig. 7b (pore size 200 × 200 μm 2 ) and 7d (pore size 500 × 500 μm 2 ), demonstrating a clear and precise 3D hierarchical structure consisting of interconnected pores and clear and distinct layers which is not possible using conventional or recently modified ES techniques47.…”
Section: Resultsmentioning
confidence: 94%
“…Electron micrographs of the two samples are shown in Fig. 7b (pore size 200 × 200 μm 2 ) and 7d (pore size 500 × 500 μm 2 ), demonstrating a clear and precise 3D hierarchical structure consisting of interconnected pores and clear and distinct layers which is not possible using conventional or recently modified ES techniques47.…”
Section: Resultsmentioning
confidence: 94%
“…The constructs showed promising results in the repair of rabbit knee joints. Recently, an EBB platform has been combined with a multi-nozzle electrospinning technique to fabricate gradient constructs with differential release rates of gentamycin sulfate (GS) and desferoxamine (DFO), which can be extended to co-print cells [76] .…”
Section: Towards Mimicking the Heterogeneity And Anisotropymentioning
confidence: 99%
“…Fabricating scaffolds with gradients of molecules and element particles for tissue engineering has drawn substantial attention. Chondroitin sulfate (CS) and gentamycin sulfate (GS) gradients have been achieved with mineralized cartilage [ 18 ] and spatiotemporal drug release [ 35 ]. Ramalingam et al reported a scaffold with amorphous calcium phosphate nanoparticles (nACP) gradient by coelectrospinning.…”
Section: Literature Reviewmentioning
confidence: 99%